Neutrosophic data formation using Gaussian filter based costas coding for wireless communication systems. (October 2019) - Ajith, A.S.; Latha, T.
Abstract: Outstanding advantages of OFDM helps high data rate communication systems such as Digital Video Broadcasting (DVB) and mobile worldwide interoperability for microwave access (mobile Wi-MAX). But, OFDM system grieves from grave issue of high PAPR. In OFDM system data output is superposition of multiple sub-carriers and leads to big data. In this case some instantaneous power output might increase greatly and become far higher than the mean power of system. In order to make Neutrosophic data for less PAPR criteria, Gaussian filter based Costas coding is proposed. This paper also proposes feeding the Orthogonal Frequency Division Multiplexed signal (OFDM) into a phase accumulator to obtain frequency modulation, with the aim of reducing the peak to average power ratio (PAPR). For associated radar with modulated waveform mentioned here can be used to enhance the performance. It is widely used to analyze the variation of the output waveform further, the implementation results using MATLAB show that the ratio of average power to peak power is reducing considerably in comparing with the conventional method. Consequently; the signal can assume to fade in a frequency selective channel without an equalizer.